Pengaruh Trend Halal Lifestyle Dan Sertifikasi Halal Terhadap Minat Beli Coffe Chain Di Indonesia Dengan Brand Ambassador Sebagai Variabel Moderasi - Maharani, Naila Cahya; Sholahuddin, M. (Paradoks : Jurnal Ilmu Ekonomi, 2025)
In today's era of globalization, business competition is getting higher and every company is competing to provide its best quality. As a country with a Muslim majority population, Indonesia has great potential for the development of the halal industry. The results of this study are 1) Halal Lifestyle has a significant influence on Purchase Intention so that the first hypothesis is accepted. 2) Halal Certificate has a significant influence on Purchase Intention so that the second hypothesis is accepted. 3) Brand Ambassador has a significant influence on Purchase Intention so that the third hypothesis is accepted. 4) Brand Ambassador can moderate the relationship between Halal Lifestyle and Purchase Intention so that the fourth hypothesis is accepted. 5) Brand Ambassador cannot moderate the relationship between Halal Certificate and Purchase Intention so that the fifth hypothesis is rejected.